A new evaluation and benchmarking framework for sentiment analysis Arabic dialectal lexicons based on multi-criteria decision making - Sameh Mohamed Sherif Ibraheim (Tanjong Malim, 2024)
A new evaluation and benchmarking framework for sentiment analysis Arabic dialectal lexicons based on multi-criteria decision making by Sameh Mohamed Sherif Ibraheim